Maintaining a Social‐Emotional Intervention and Its Benefits for Institutionalized Children. Issue 5 (1st April 2013) - McCall, Robert B.; Groark, Christina J.; Fish, Larry; Muhamedrahimov, Rifkat J.; Palmov, Oleg I.; Nikiforova, Natalia V.
Abstract : This article reports the maintenance of one of the largest interventions conducted in St. Petersburg (Russian Federation) orphanages for children birth to 4 years using regular caregiving staff. One orphanage received training plus structural changes, another training only, and a third business as usual. The intervention produced substantial differences between these institutions on the Home Observation for Measurement of the Environment (HOME) Inventory and on the Battelle Developmental Inventory scores for children. These institutional differences in HOME scores ( N = 298) and Battelle scores for children ( N = 357) departing the institutions for families in St. Petersburg and the United States were maintained for at least 6 years after the intervention project. This result may be associated with certain features of the intervention and activities conducted during the follow‐up interval.